A critical evaluation of the constitutional protection of fundamental liberties in Malaysia : the meaning of "law" / Sharon K. Chahil - K. Chahil, Sharon (Faculty of Administratron and Law, 2004)
The purpose of this analysis is to evaluate the extent to which the definition of "law" in Articles 5(1), 13(1) and other fundamental liberties provisions of the Federal Constitution provides for the element of natural justice. The importance of this endeavour lies in the fact that in the absence of the element of natural justice, "law" may be utilised to wantonly abrogate the fundamental liberties provisions stipulated in the Federal Constitution.